Attraction of three-star hotel through alternative entertainments / Rashidi Othman … [et al.] - Othman, Rashidi; Hashim, Khairusy Syakirin Has-Yun; Mat Daud, Zainab ‘Aqilah; Jamaludin, Mohd Aizat; Mahamod, Lukman Hakim; Ahmad Fadzlillah, Nurrulhidayah (Academy of Contemporary Islamic Studies (ACIS), 2017)
Hotel ratings are used to classify hotels according to their quality. The objective of hotel ratings is to focus on the hotel experience as a whole. Three star hotels and above attract their guests by providing various types of services and facilities. Hotels are independently assessed in traditional systems and rely heavily on the facilities provided. This standard discriminates people with a smaller budget to experience certain services. In fact, three-star hotels can provide certain facilities and services in such a way to attract more people. This study critically discusses on the implementation of entertainment services existing in three-star hotels. Observation has been used to analyse the implementation of entertainments in the three-star hotels. The study demonstrates that most three-star hotels provide very little entertainment due to some limitations. In conclusion, three-star hotels can provide more entertainment that is shariah compliant to attract guests despite the space limitation and financial constraint.